Pengaruh Edukasi Presentasi dan Brosur Terhadap Pengetahuan Swamedikasi Pencegahan Anemia - Putu Ika Indah indraswari; Putu Ayu Ratih Listiani (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2026)
Anemia is one of the most common health problems among adolescents and has the potential to reduce quality of life and academic performance. The prevention of anemia can be achieved through rational self-medication; however, its effectiveness is highly dependent on an individual's level of knowledge. Therefore, this community service activity was conducted to analyze the effect of educational interventions using presentations and brochures on the level of knowledge regarding self-medication for anemia prevention among twelfth-grade Pharmacy students at SMK Kesehatan Bintang Persada. The study employed a one-group pretest-posttest design by assessing participants' knowledge before and after the educational intervention. The educational materials were delivered through presentations accompanied by brochures as supporting media, while data were collected using questionnaires. The results of the activity showed that before education, an average of 78.1% of participants understood anemia. After the intervention, all participants (100%) achieved a good level of knowledge. This improvement indicates that education delivered through a combination of presentations and brochures effectively enhanced students' understanding of self-medication for anemia prevention. Similar programs are recommended to be implemented continuously in school settings as part of adolescent health promotion and may be further developed by incorporating more innovative educational media to improve learning effectiveness. These findings confirm that educational interventions are an effective strategy for improving adolescents' knowledge of self-medication for anemia prevention